2023
DOI: 10.3390/educsci13080835
|View full text |Cite
|
Sign up to set email alerts
|

First Year Engineering Students’ Difficulties with Math Courses- What Is the Starting Point for Academic Teachers?

Marios Charalambides,
Rita Panaoura,
Eleni Tsolaki
et al.

Abstract: The discussion about first-year engineering students’ difficulties in mathematics is continuous in the fields of engineering, mathematics and higher education. The present study aimed to examine the initial barriers academic math teachers need to have in mind if they want to improve students’ performance in engineering math courses through appropriate teaching practices in order to face their initial interindividual differences. During the first phase of the study, we examined first year engineering students’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The analysis of the students' responses to the items about the students' beliefs resulted in five factors, which explained the 67.75% of the total variance and the respective analysis of the items about self-efficacy beliefs and attitudes towards mathematics resulted in three factors, which explained the 73.56% of the total variance. The content analysis of the items (Charalambides et al, 2023) of the eight factors resulted into the following factors: F1. Success in mathematics (seven items, e.g., some people are not able to learn mathematics), F2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the students' responses to the items about the students' beliefs resulted in five factors, which explained the 67.75% of the total variance and the respective analysis of the items about self-efficacy beliefs and attitudes towards mathematics resulted in three factors, which explained the 73.56% of the total variance. The content analysis of the items (Charalambides et al, 2023) of the eight factors resulted into the following factors: F1. Success in mathematics (seven items, e.g., some people are not able to learn mathematics), F2.…”
Section: Resultsmentioning
confidence: 99%
“…In order to examine the two posed research questions, we had developed (a) a questionnaire about students' affective behavior towards mathematics (presented at Charalambides et al, 2023) and (b) a test about their initial mathematical performance before attending introductory course AMAT111.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Körei, Sz. Szilágyi (5) and the parametric equations of the curve drawn by the robot should be given immediately, knowing the parameters of the current configuration, i.e. the diameter of the mounted gears and the position of the pole.…”
Section: Principles Of Steam-based Learning Methodsmentioning
confidence: 99%
“…However, digital content alone is insufficient for Generation Z students to sustain attention. Several studies have shown that first-hand experiences are the best way to achieve optimal learning outcomes for today's university students [1,5,10,16]. This explains the re-emergence of hands-on and explorable models in universities and increased projects involving physical activity in mathematics courses.…”
Section: Introductionmentioning
confidence: 99%